Respuestas

  • Usuario de Brainly
2014-03-03T20:26:56+01:00
  seny              1-cosy          multiplico y divido por ( 1 -cosy)
-------------- =  ----------------
1 +cosy          seny

seny          1 -cosy             1-cosy          multiplico y divido por ( 1 -cosy)
------------- * --------------=     ----------------
1 +cosy      1 -cosy            seny

seny (1-cosy)            1-cosy       como  sen^2y = 1-cos^2y
---------------------- =  ------------------
1-cos^2y                    seny

seny (1-cosy)       1-cosy
---------------------- = --------------
 sen^2y                  seny
 
1-cosy       1-cosy
-----------  = ------------
seny          seny